2021
DOI: 10.1093/ehjacc/zuab038
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of patients with different clinical presentations of high-risk pulmonary embolism

Abstract: Aims The 2019 European Society of Cardiology (ESC) guidelines provide a revised definition of high-risk pulmonary embolism (PE) encompassing three clinical presentations: Cardiac arrest, obstructive shock, and persistent hypotension. This study investigated the prognostic implications of this new definition. Methods and results Data from 784 consecutive PE patients prospectively enrolled in a single-centre registry were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“… 3 , 21 Furthermore, altered mental status was an independent predictor [OR 9.1] of a life-threatening adverse outcomes in PE patients. 22 Using this information, we proposed a new ICU-sPESI mortality prediction score by adding these clinical variables to the original sPESI score. This novel score demonstrated improved discrimination of mortality risk compared to PESI and sPESI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 , 21 Furthermore, altered mental status was an independent predictor [OR 9.1] of a life-threatening adverse outcomes in PE patients. 22 Using this information, we proposed a new ICU-sPESI mortality prediction score by adding these clinical variables to the original sPESI score. This novel score demonstrated improved discrimination of mortality risk compared to PESI and sPESI.…”
Section: Discussionmentioning
confidence: 99%
“…These markers were chosen based on prior studies showing their independent association with PE mortality. 3 , 21 , 22 …”
Section: Methodsmentioning
confidence: 99%
“…від вихідного рівня без причин, яке триває понад 15 хв, і є основою стратифікації пацієнтів з гострою ТЕЛА до групи високого ризику розвитку несприятливих подій згідно із сучасними рекомендаціями [1]. Наразі встановлено, що клінічний перебіг ТЕЛА у групі високого ризику є найтяжчим, а прогноз вкрай несприятливим, госпітальна летальність, за даними різних досліджень, серед цих пацієнтів може становити від 25,4 до 70 % [3,4]. Проте залишається недостатньо вивченим питання щодо додаткових клініко-анамнестичних та інструментальних чинників, які можуть бути пов'язані з прогнозом у хворих на ТЕЛА високого ризику.…”
Section: оригінальні дослідження / Original Researchesunclassified
“…Recent data suggest that early risk stratification of acute PE could be improved by taking account of additional covariates, especially in high-risk PE. Data from 784 consecutive PE patients prospectively enrolled in a single-center registry suggested that the use of an optimized venous lactate cut-off value (i.e., 3.8 mmol/L vs. 2.3 mmol/L with the current definition) to diagnose obstructive shock made it possible to distinguish risk of in-hospital adverse outcomes between patients with shock and persistent hypotension (21.4% vs. 9.5%, respectively), resulting in a net reclassification improvement (0.24 ± 0.08; p = 0.002) [ 78 ]. Moreover, we previously demonstrated that the addition of renal dysfunction on top of the current ESC risk stratification improved overall model performance, yielding 18% reclassification of overall predicted mortality, including reclassification across intermediate–high-risk to high-risk PE in 15.8% of eligible patients [ 79 ].…”
Section: Current Controversies Warranting Further Researchmentioning
confidence: 99%